Transcriptomic analysis of the spatiotemporal axis of oogenesis and fertilization in C. elegans - Su, Yangqi; Shea, Jonathan; Destephanis, Darla; Su, Zhengchang (Frontiers in Cell and Developmental Biology, 2024)
C. elegans hermaphrodite presents a unique model to study the formation of oocytes. However, the size of the model animal and difficulties in retrieval of specific stages of the germline have obviated closer systematic studies of this process throughout the years. Here, we present a transcriptomic level analysis into the oogenesis of C. elegans hermaphrodites. We dissected a hermaphrodite gonad into seven sections corresponding to the mitotic distal region, the pachytene region, the diplotene region, the early diakinesis region and the 3 most proximal oocytes, and deeply sequenced the transcriptome of each of them along with that of the fertilized egg using a single-cell RNA-seq (scRNA-seq) protocol. We identified specific gene expression events as well as gene splicing events in finer detail along the gonad and provided novel insights into underlying mechanisms of the oogenesis process. Furthermore, through careful review of relevant research literature coupled with patterns observed in our analysis, we delineate transcripts that may serve functions in the interactions between the germline and cells of the somatic gonad. These results expand our knowledge of the transcriptomic space of the C. elegans germline and lay a foundation on which future studies of the germline can be based upon.